2019
DOI: 10.3390/ma12081309
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Compression Behavior of Cement Mortar and Its Damage-Constitutive Model Based on Energy Theory

Abstract: The mechanical properties of mortar materials in construction are influenced both by their own proportions and external loads. The trend of the stress–strain curve in cracks compaction stage has great influence on the relationship between the strength and deformation of cement mortar. Uniaxial compression tests of mortar specimens with different cement–sand ratios and loading rates were carried out, and the stored and dissipated energies were calculated. Results indicated that the elastic modulus and strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…First, roof‐and‐floor movement evolution and transfer bearing mechanism of gob‐side entry have been revealed. Roof movement is divided into three stages: early stage, transition stage, and later stage; and two basic forms: roof rotation and subsidence . On this basis, Zhang et al proposed the concept of a wedge‐shaped bearing area and further clarified the transmission and bearing mechanism of the gob‐side roof.…”
Section: Introductionmentioning
confidence: 99%
“…First, roof‐and‐floor movement evolution and transfer bearing mechanism of gob‐side entry have been revealed. Roof movement is divided into three stages: early stage, transition stage, and later stage; and two basic forms: roof rotation and subsidence . On this basis, Zhang et al proposed the concept of a wedge‐shaped bearing area and further clarified the transmission and bearing mechanism of the gob‐side roof.…”
Section: Introductionmentioning
confidence: 99%
“…This research demonstrates that the key parameters determined through a numerical simulation satisfactorily meet the production requirements and provide a reference for ensuring safe production in deep mining conditions. about 100-500 m, the microstructures, basic mechanical characteristics, and engineering responses of coal and rock have changed significantly in response to the "three highs and one disturbance" environment [10][11][12][13]. The main features are that the surrounding rock has a large deformation, high deformation speed, long deformation duration, and rheological characteristics.…”
mentioning
confidence: 99%
“…A rock burst is a common dynamic disaster often accompanied by sudden, quick, and violent ejection of coal or rock during coal excavation that happens in complex ways under special conditions . Many case studies have revealed that the failure of the layer‐crack structure is closely related to rock burst occurrence, especially for brittle rock or coal mass, as shown in Figure . A layer‐crack structure refers to coal or rock rib cut by macrotensile cracks parallel or subparallel to the rib surface at a certain depth due to excavation unloading.…”
Section: Introductionmentioning
confidence: 99%